Parent-child relationship in Serbia (Vojvodina) in historical perspective and today - Kovaček Stanić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
In this paper author have studied out and analyzed family law relations between parents and children in Vojvodina in the period between two world wars according to acts, court precedent, private law rules and legal doctrine. The author have studied family law relations between parents and children in contemporarz Serbia and in European law. In historical perspective in Vojvodina (including Medjumurje and Prekomurje) the Hungarian law (acts) was in use, except in Srem and Vojna granica where the Austrian law was in use. The issues of family status of children, in other words, the rules of establishing and contesting paternity, parental rights and duties, exercise of parental rights were analyzed. The father had paternal authority and priority role if the child was born in wedlock. If the child was born out of wedlock, mother had priority role in exercising rights and duties. If parents were divorced or separated the priority role had the parent who had custody of the child, the other parent had visitation rights. In the second part of this paper the court cases in parent-child relation in twentieth and thirtieth years of XX century kept in Archive of Vojvodina, were analyzed. In particular, the author has studied cases in which the court made a decision according to court precedent, private law rules and legal doctrine.